Mindsets as sources of L2 speaking anxiety and self-confidence: the case of international teaching assistants in the U.S. Issue 3 (27th May 2022) - Ozdemir, Esra; Papi, Mostafa
ABSTRACT: Second language (L2) researchers have often studied how L2 speaking anxiety and self-confidence influence various aspects of the language learning process whereas the sources of these emotions have remained under-explored. Drawing on Dweck's (1999) theory of motivation, the present study examined L2 learners' mindsets (beliefs about the malleability of their language learning intelligence) as potential sources of L2 speaking anxiety and L2 self-confidence. Questionnaire data was collected from 92 international teaching assistants who use English as a second language in their teaching practice at a U.S. university. Multiple regression results showed that whereas the Fixed L2 Mindset (the belief that language learning ability cannot change) positively predicted L2 Speaking Anxiety, the Growth L2 Mindset (the belief that language learning ability can grow) positively predicted L2 Speaking Self-Confidence, confirming the hypothesized relationships between the conceptual principles of the mindsets theory and the nature of L2 anxiety and self-confidence. Theoretical and educational implications and future research directions are discussed.